Regulacje stanów nadzwyczajnych w ustawie zasadniczej - Kordik, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The present publication only to a minimal range indicates the regulations state a specific threat, in light of the provisions of the Constitution. The idea of the same Article, or goal is not only to present the said matter, but also a better understanding of it. In the author’s topic is worthy of attention because these issues border on the universe of the modern world.
Keywords: stany nadzwyczajne; regulacje prawne; konstytucja